An Assessment of the Impact of Information Communication Technology (ICT) On the Administration of Public Records: A Case Study of the Bolgatanga Municipal Assembly in the Upper East Region of Ghana-West Africa - Yinimi, Ruth; Akanpaadgi, Emmanuel (International Journal of Business, Economics and Management, 2015)
The study assessed the impact of Information Communication Technology (ICT) on the administration of public records in public institutions with the Bolgatanga Municipal Assembly as a case study. The researchers adopted both quantitative and qualitative research approaches. The data was gathered using a self-administered questionnaire as all the respondents are literates. The purposive sampling technique was used to select a sample size of forty-eight (48) staff of the Assembly. Simple descriptive statistics such as frequency tables and charts were employed in presenting the results after using Microsoft Excel to analyse the data. The research revealed that the type of ICT facilities being used by staff of the Assembly included computers, internet, telephones and fax machines. Majority of the respondents mentioned that staff usage of ICT facilities depended on whether they are ICT literates or not. Other factors mentioned were the availability of certain ICT facilities and knolwdege of their existence as a trigger to their usage. Finally, the results confirmed that indeed the use of ICT facilities had a positive impact on the administration of public records in the Bolgatanga Municipal Assembly. The benefits derived by the Assembly included; increased productivity, security of public records, personal development and easy communication among staff of the Assembly and between the Assembly and other organisations or individuals.